Pemanfaatan PGPR Akar Rumput Belulang dan Pupuk Kandang Sapi untuk Meningkatkan Pertumbuhan dan Hasil Bawang Merah - Noor, Risyadilla Amalia; Setiyono, Setiyono; Patricia SM, Susan Barbara (Agrosains : Jurnal Penelitian Agronomi, 2022)
Shallot (Allium ascalonicum L.)  is a plant species sensitive to environmental conditions. Although, Shallot can grow optimally in the dry season, in the rainy season the production of Shallot tends to decrease. Efforts made by farmers to overcome this are by increasing the dose of inorganic fertilizers. If it continues, it will have a negative impact on the environment. The application of Plant Growth Promoting Rhizobacteria (PGPR) and cow manure has increased the production of shallots grown out of season. This study used the basic pattern of 3x3 factorial Completely Randomized Block Design (RCBD) and was repeated 3 times. The first factor was the PGPR concentration of Belulang's roots which consisted of 3 levels, namely P0: 0 ml/L, P1: 10 ml/L, P2: 20 ml/L. Factor 2 doses of cow manure consisting of 3 levels, namely N0: 0 tons/ha, N1: 10 tons/ha, N2: 20 tons/ha. Further test using Duncan's Multiple Distance Test at 5% level. The results showed that there was no interaction between the two treatments, but separately the two treatments had an effect on the growth and yield of shallots. a concentration of 10 ml/L PGPR of belulang's roots and cow manure at a dose of 20 tons/ha is a good treatment to be recommended in this study.